THE EXTERNAL AND INTERNAL IMAGES OF JUDGES AND COURTS - Valickas, Gintautas; Šeršniovaitė, Dovilė; Mikuličiūtė, Vita (Teisė, 2016)
Article examines the character, similarities and differences of the image (separate it’s aspects) of judges and courts perceived by judges (n = 171) and general public representing different age groups (n = 1186), as well as the relationships among the image of judges and courts, experience accumulated by participants, and socio-demographic characteristics.The participants completed the “Image of Judges and Courts” questionnaire developed by us. Findings showed that the image of judges and courts (the environmental, service, and social aspects of the image) perceived by all external groups (outsiders) and by judges (insiders) was positive. Participants of all external groups gave the most favourable opinion about the image of environment, less favourable opinion about the image of services, and the relatively least favourable opinion about the social image, while judges gave the highest appraisal to the image of services, lower appraisal to the social image, and the lowest appraisal to the image of environment. Youngest (14–17 year old) participants, compared to all older ones (18–25 year olds, 26–49 year olds and 50–86 year olds), appraised all aspects of the image of judges and courts much more favourably. Appraisals of the image of judges and courts given by external groups were related to various factors, such as gender, education, acquired knowledge of the law, personal or family members’ / acquaintances’ participation in court hearings, etc. Judges, in comparison with participants from all external groups (14–17 year olds, 18–25 year olds, 26–49 year olds, and 50–86 year olds), gave more favourable opinions about the service and social images, however, compared to 14–17 year old participants, they rated the environmental image less favourably. Much higher ratings given to the service and social images by judges, compared to participants representing all external groups, may be related either to inadequately overstated evaluation on the part of judges (especially women), or to inadequately understated evaluation on the part of general public, or to both. In any case, such gap between the ratings of the service and social images by judges and general public is a reason for concern.